The welfare of the laboratory mouse : comparison in development of mouse pups in three different individual ventilated cage (IVC) systems - Wirf, Malin (SLU/Dept. of Animal Environment and Health (until 231231), 2013)
Today the individual ventilated cage system (IVC-system) is a commonly used housing system for mice in research facilities. IVC systems have HEPA- filters and are designed to control both supply and exhausted air at cage level, as well as temperature and relative humidity in the cages. This creates an optimal environment for the mouse and at the same time a protection against the risk of cross-infection between cages and the outside environment. The aim of this study was to evaluate the health and welfare of breeding females and pups of two different strains of laboratory mice (NMRI nude mice and C57BL/6N) in three different kinds of IVC-systems; Arrowmight, Allentown and Tecniplast. The NMRI nude (Nu) females gave birth to 18 litters in Allentown, 16 litters in Arrowmight and 15 litters in Tecniplast. The C57 females gave birth to 16 litters in Allentown, 17 litters in Arrowmight and 16 litters in Tecniplast. With these litters we performed tests on both the pups and the females. We tested the pups development. The females bodyweight was registered on the same days. Food and water consumption were registered from gestation week 2 to lactation week 3. Nest location and nest score were registered in all systems. We found one difference in Nu females; they weigh less in Allentown (p<0.01) compared to Arrowmight and Tecniplast systems at day 14. The Nu females in Allentown ate and drank less compared to Arrowmight and Tecniplast and it was a significant difference in food consumption at lactation week 2 (p<0.05) and water consumption (p<0.05) lactation week 1. Nu pups development and weight gain in Allentown was unaffected. No big differences between pups development were found between the IVC-systems but we could see a clear strain difference between Nu and C57. In conclusion, there were no major differences between the different IVC systems in this study. The differences that we did find could have been due to this experimental setup, e.g. the different number of Air changes per hour (ACH) in the different systems. We used the manufacturers recommendations for ACH in this study.